NEW APPLICATIONS OF THE METATHEOREM IN ORDERED FIXED POINT THEORY - Park, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2024)
Our aim in this paper is to and new applications of our long- standing 2023 Metatheorem. In fact, a certain particular form of Metatheorem on fixed point theorems characterizes metric completeness. Moreover, classical theorems due to Banach, Rus-Hicks-Rhoades, Nadler, Covitz-Nadler, Oettli- Thera, Edelstein, Turinici, Taskovic, Khamsi and ourselves are equivalently formulated or improved by applying Metatheorem.